Analisis Implementasi Prinsip Pembelajaran Mendalam pada Pelaksanaan Pembelajaran Matematika Materi Lingkaran di SMK Kelas XI - Dea Puspitasari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to describe the implementation of deep learning principles in mathematics learning on circle material for eleventh-grade vocational high school students. This study employed a qualitative descriptive approach conducted at SMKS Al Hasan Jember. The subjects consisted of one mathematics teacher and three eleventh-grade Accounting and Institutional Finance students selected through purposive sampling based on high, medium, and low academic ability categories. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, conclusion drawing, and triangulation. The results showed that the implementation of deep learning principles had led to active student involvement through questioning activities, discussions, collaboration, and positive classroom interactions. The teacher also attempted to maintain students’ focus and create a comfortable learning atmosphere. However, several aspects had not been optimally implemented, such as connecting the material to real-life contexts, involving students in direct practice, and developing students’ creativity in completing tasks. In addition, not all students showed confidence in expressing opinions, explaining concepts independently, or participating in reflection activities. Therefore, mathematics learning on circle material had reflected active and joyful learning, but meaningful learning and equal student involvement still need to be improved.
Keywords: Deep learning principles; Merdeka curriculum; Mindful learning; Meaningful learning; Joyful learning; Learning implementation